Documents on Capitation: Casa dos Contos Collection at the Brazilian National Library Foundation - Mont Serrath, Pablo Oller (Revista do Instituto Histórico e Geográfico Brasileiro, 2024)
The Casa dos Contos Collection at the Brazilian National Library Foundation has one of the most important document database on taxation in Brazil. It includes more than 12,000 documents related to the region of Minas Gerais between 1701 and 1889. It is fully digitized and accessible online on the SophiA platform. Among the manuscript documents of the collection, the Registration Book of Ordinances and Orders Issued to this Office (in Vila Rita) stands out. It includes documents dated between 1735 and 1751 that deal which with the socalled capitation, a tax modality which required that one-fifth of the gold mined in captaincy of Minas Gerais be sent to the colonial government as taxes paid to the Portuguese Crown. In the paper, we transcribe the following documents from the book: Hereby we appoint Domingos da Silva as Intendant of this Village, of July 14, 1735; Control of Capitation Forms and Shipment of Production Maps etc., of April 25; 1736; Regiment that the Governor’s Assistant Must Observe for the Good Revenue from Gold and Capitation Forms, undated; and Registration of the Capitation Regiment, of January 14, 1736.